2019
DOI: 10.1002/lt.25318
|View full text |Cite
|
Sign up to set email alerts
|

Plasma From Patients Undergoing Liver Transplantation Is Resistant to Anticoagulant Activity of Soluble Thrombomodulin

Abstract: This study suggests that ART-123 is unlikely to provoke bleeding in patients undergoing liver transplantation as proposed clinical dosages have a virtually absent anticoagulant effect in these patients. Clinical studies are required to confirm safety of ART-123 and efficacy on alleviating I/R injury during liver transplantation. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Given the importance of acute liver dysfunction in explaining risk for microvascular thrombosis (by predisposing to reduced levels of PC and AT), it is possible that rhsTM might not decrease SPG risk in patients with shock liver. Indeed, Burlage and coworkers 70 found that plasma from patients undergoing liver transplantation was resistant to anticoagulant action of ART-123, an effect they attributed to decreased levels of PC and protein S (cofactor for APC) in patients with severe liver disease.…”
Section: Thrombomodulin Concentrates As a Treatment For Dicmentioning
confidence: 99%
“…Given the importance of acute liver dysfunction in explaining risk for microvascular thrombosis (by predisposing to reduced levels of PC and AT), it is possible that rhsTM might not decrease SPG risk in patients with shock liver. Indeed, Burlage and coworkers 70 found that plasma from patients undergoing liver transplantation was resistant to anticoagulant action of ART-123, an effect they attributed to decreased levels of PC and protein S (cofactor for APC) in patients with severe liver disease.…”
Section: Thrombomodulin Concentrates As a Treatment For Dicmentioning
confidence: 99%